(untitled) (Eurasian Journal of History, Geography and Economics, 2026)
This article provides a comprehensive analysis of the socio-economic and institutional development processes in Karshi District of Kashkadarya region during the period 2005– 2025. The study examines the gradual diversification of the regional economy from an agrarian orientation, the development of industrial and service sectors, the modernization of infrastructure, and the institutional reforms implemented in the governance system. It also highlights the impact of state programs carried out within the framework of the “New Uzbekistan” reforms on district development, as well as the importance of the cluster system, digitalization processes, and investment policy. As a result of the study, the transition of Karshi District to a modern multi-sectoral economy is scientifically generalized, and conclusions regarding its future development trends are formulated